Leaf mycobiome and the success of Hymenoscyphus fraxineus in completing its life cycle depend on the canopy position of common ash - Long, Feng; Kosawang, Chatchai; Nielsen, Lene R.; Hietala, Ari M. (Frontiers in Microbiology, 2025)
IntroductionCommon ash (Fraxinus excelsior) is threatened by an invasive Asian-origin ash dieback pathogen, Hymenoscyphus fraxineus. The pathogen establishes leaf infection with the aid of wind-borne ascospores, followed by mycelial spread from the leaf into the shoot before autumn senescence. Whether the mycobiome in living leaves and the fructification success of this fungus in overwintered leaves differ between saplings and different crown layers of large trees is poorly understood.MethodsWe pursued these questions by ITS1-based amplicon sequencing and recording of the number of pathogen ascocarps formed on leaf debris.ResultsFungal diversity (Shannon and Simpson indices) and richness (Chao1) in leaves differed significantly between saplings and the upper or lower light canopy of large trees. Saplings showed the most diverse fungal communities, and the upper light canopy had the least diverse ones. In saplings, the two most dominant fungi were an unknown ascomycete and H. fraxineus (combined read proportion 27.2%), while this unknown ascomycete and genus Aureobasidium were the most common fungi in upper (combined read proportion 70.2%) and lower (combined read proportion 52.0%) light canopy of large trees. The number of H. fraxineus-like ascocarps produced on petiole/rachis tissues after overwintering was, on average, 7.5 for saplings and 1.4 for large trees (canopy layers combined); saplings differed significantly from most of the large trees in this respect. Leaves from large trees with no defoliation also produced H. fraxineus-like ascocarps.DiscussionThe potential interactions between H. fraxineus and phyllosphere fungal community and the implications of our findings to management of ash stands are discussed.